A Computational Approach Identifies Immunogenic Features of Prognosis in Human Cancers - Manoharan, Malini; Mandloi, Nitin; Priyadarshini, Sushri; Patil, Ashwini; Gupta, Rohit; Iyer, Laxman; Gupta, Ravi; Chaudhuri, Amitabha (Frontiers in Immunology, 2018)
A large number of tumor intrinsic and extrinsic factors determine long-term survival in human cancers. In this study, we stratified 9120 tumors from 33 cancers with respect to their immune cell content and identified immunogenomic features associated with long-term survival. Our analysis demonstrates that tumors infiltrated by CD8+ T cells expressing higher levels of activation marker (PD1hi) along with TCR signaling genes and cytolytic T cell markers (IL2hi/TNF-αhi/IFN-γhi/GZMA-Bhi) extend survival, whereas survival benefit was absent for tumors infiltrated by anergic and hyperexhausted CD8+ T cells characterized by high expression of CTLA-4, TIM3, LAG3 and genes linked to PI3K signaling pathway. The computational approach of using robust and highly specific gene expression signatures to deconvolute the tumor microenvironment has important clinical applications, such as selecting patients who will benefit from checkpoint inhibitor treatment.